Characteristics of Indonesian Adolescents who had Experienced Pregnancy Under the Age of 20 Years: Basic Health Research 2018 - Ratih Indraswari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2021)
Background: As well as other countries, Basic Health Research 2018 (Riskesdas) reported that adolescent pregnancies (aged under 20 years) occurred in almost all provinces in Indonesia. More than 60,000 Indonesian females experienced pregnancy at a young age. Objective: This study aims to analyze the characteristics of Indonesian women who had been pregnant under the age of 20 years. Methods: This study used a quantitative study with a cross-sectional design, the data processed was from Indonesian Basic Health Research 2018. The subjects were 67,392 women who experienced their first pregnancy under the age of 20 years. The independent variables of the study included the respondent's domicile, age, education level, and occupation. The dependent variable was the age at first pregnancy. All variables were analyzed using univariate, bivariate, and multivariate analysis. Results: Almost all (95.4%) Indonesian women who had experienced adolescent pregnancy were in the age range of 14-19 years when they were first pregnant. Most of the respondents lived in rural areas (68.1%), were in late adulthood (32.9%) when the survey was conducted, had completed primary school education (38.7%), and were not working (47.9%). Domicile, age, education, and occupation were related significantly to the age at which they were first pregnant (P-Value = 0.0001). Education affected the age at first pregnancy in women with a history of adolescent pregnancy (OR = 2.215). Conclusion: Adolescent with low education level is 2.2 riskier to have early pregnancy than an adolescent with high-level education. The government needs to make it a priority and seriously provide provision of reproductive health education among children before they get into their adolescence phase.